Evidence for a recent horizontal transmission and spatial spread of Wolbachia from endemic Rhagoletis cerasi (Diptera: Tephritidae) to invasive Rhagoletis cingulata in Europe. Issue 15 (12th July 2013) - Schuler, Hannes; Bertheau, Coralie; Egan, Scott P.; Feder, Jeffrey L.; Riegler, Markus; Schlick‐Steiner, Birgit C.; Steiner, Florian M.; Johannesen, Jes; Kern, Peter; Tuba, Katalin; Lakatos, Ferenc; Köppler, Kirsten; et al.
Abstract: The widespread occurrence of Wolbachia in arthropods and nematodes suggests that this intracellular, maternally inherited endosymbiont has the ability to cross species boundaries. However, direct evidence for such a horizontal transmission of Wolbachia in nature is scarce. Here, we compare the well‐characterized Wolbachia infection of the European cherry fruit fly, Rhagoletis cerasi, with that of the North American eastern cherry fruit fly, Rhagoletis cingulata, recently introduced to Europe. Molecular genetic analysis of Wolbachia based on multilocus sequence typing and the Wolbachia surface protein wsp showed that all R. cingulata individuals are infected with w Cin2 identical to w Cer2 in R. cerasi . In contrast, w Cin1, a strain identical to w Cer1 in R. cerasi, was present in several European populations of R. cingulata, but not in any individual from the United States. Surveys of R. cingulata from Germany and Hungary indicated that in some populations, the frequency of w Cin1 increased significantly in just a few years with at least two independent horizontal transmission events. This is corroborated by the analysis of the mitochondrial cytochrome oxidase II gene that showed association of w Cin1 with two distinct haplotypes in Germany, one of which is also infected with w Cin1 in Hungary. In summary, our study provides strong evidence for a very recent inter‐specific Wolbachia transmission with a subsequent spatial spread in field populations.